Chinese Saving Rates from 1953 to 2012: Trends, Compositions and Prospects. (17th May 2016) - Zhou, Shaojie; Zhang, Junsen
Abstract: This study conducts a long‐run analysis on the trends and components of Chinese saving rates from 1953 to 2012. We identify two structural changes in aggregate saving rates around 1978 and 2001, and examine them through a decomposition analysis of the income distribution and sector‐specific saving rates. The following key findings are obtained. First, the major trends and compositions of Chinese saving rates changed markedly over the period considered, which explains the changes of aggregate saving rates with the dramatic economic transition from a planned economy to a market‐oriented economy. Second, we investigate the surge in aggregate saving rates from 2001 to 2012 based on a series of institutional factors, such as the evolving labour market, domestic economic policy adjustments and changes in external economic conditions caused by China's accession to the World Trade Organization in 2001 and the 2008 global financial crisis. Finally, we present the future prospects for the high aggregate saving rates in China based on several evolving economic, demographic and policy trends. We argue that Chinese saving rates have peaked in recent years and that a declining trend is expected, which will contribute to the economic rebalancing of the country.